Selenium Status in Diet Affects Nephrotoxicity Induced by Cisplatin in Mice - Shuang Liu; Xing Wen; Qihan Huang; Minghui Zhu; Jun Lu (Antioxidants, 2022)
Cisplatin is one of the most active chemotherapy drugs to treat solid tumors. However, it also causes various side effects, especially nephrotoxicity, in which oxidative stress plays critical roles. Our previous studies found that cisplatin selectively inhibited selenoenzyme thioredoxin reductase1 (TrxR1) in the kidney at an early stage and, subsequently, induced the activation of Nrf2. However, the effects of selenium on cisplatin-induced nephrotoxicity are still unclear. In this study, we established mice models with different selenium intake levels to explore the effects of selenoenzyme activity changes on cisplatin-induced nephrotoxicity. Results showed that feeding with a selenium-deficient diet sensitize the mice to cisplatin-induced damage, whereas selenium supplementation increased the activities of selenoenzymes TrxR and glutathione peroxidase (GPx), changed the renal cellular redox environment to a reduced state, and exhibited protective effects. These results demonstrated the correlation of selenoenzymes with cisplatin-induced side effects and provided a basis for the potential approach to alleviate cisplatin-induced renal injury.